Robotic tracheal resections on veno-venous extracorporeal membrane oxygenation with 23-hour length of stay and without guardian chin stitch - McCormack, Ashley J.; Chang, Stephanie H.; Smith, Deane E.; Geraci, Travis C.; Phillips, Katherine G.; Cerfolio, Robert J. (Frontiers in Surgery, 2026)
ObjectiveMid-to-distal tracheal surgery for cancer can be safely performed minimally invasively with a one-day length of stay, avoiding a guardian chin suture, and ensuring a R0 resection in select patients.MethodsThis is a retrospective technical review of the largest series to date of patients with mid-to-distal tracheal cancers. All were offered a right robotic approach using veno-venous extracorporeal membrane oxygenation (VV ECMO) support via percutaneous right internal jugular vein and right common femoral vein access.ResultsFrom May 2019 to April 2024, five consecutive patients (3 men, 2 women; aged 11, 29, 37, 40, and 74 years) presented with a mid-to-distal tracheal cancer. All underwent right robotic mid-distal tracheal resections on VV ECMO for primary tracheal cancers. All patients had an end-to-end tracheal anastomosis and R0 resection and all avoided: systemic heparinization, suprahyoid release maneuvers and a postoperative guardian chin stitch. Median operative time was 258 min (range 227–292). All patients tolerated the operations well and were discharged home on the morning of postoperative day 1. There was no minor or major morbidity, no 30 or 90-day mortality, and no re-admissions. Two patients complained of cough. All had R0 resections and to date none have evidence of recurrent disease or stricture.ConclusionResection of mid-to-distal primary tracheal cancers can be performed safely and efficiently via a right robotic approach while on VV ECMO with little to no morbidity or mortality and require only an overnight hospital stay. The techniques used to perform the operation and achieve these results are described.